PVT1 Promotes Cancer Progression via MicroRNAs - Wang, Wenxi; Zhou, Ruoyu; Wu, Yuwei; Liu, Yicong; Su, Wenjia; Xiong, Wei; Zeng, Zhaoyang (Frontiers in Oncology, 2019)
Noncoding RNA (ncRNA) plays a regulatory role in a variety of cellular activities. And long noncoding RNA (lncRNA) is one of the important kinds of ncRNA. Previous studies have shown that various lncRNAs are involved in the progression of cancer. LncRNA plasmacytoma variant translocation 1 (PVT1) is a newly discovered oncogenic factor that has been confirmed to be overexpressed in many cancer cells. Moreover, the role of PVT1 in cancer development is closely linked to microRNAs (miRNAs). PVT1 can act as a "sponge" for miRNAs to inhibit their activities, thereby affecting proliferation, invasion, and angiogenesis of cancer. In addition, PVT1 itself can be spliced and processed into several miRNAs such as miR-1204 and miR-1207, which can also regulate the development of cancer. This review summarizes various pathways through which PVT1 regulates the progression of cancer via miRNAs. We also propose additional regulatory mechanisms of PVT1 and their potential clinical applications.